The Effect of Non-Physical Work Environment and Organizational Culture on Employee Performance and Commitment to the Organization as Intervening Variables - Satria, Yudi Wahyu; Muharam, Hari; Yusnita, Nancy (Peneliti.net, 2024)
The phenomenon that occurs at PT Eka BogaInti in the Bogor area shows a significant decrease in employee performance. Based on data on the average achievement of employee Key Performance Indicator (KPI) in 2022 and 2023, there is a shortfall of 21.31% of the expected target. This problem is thought to be caused by a non-physical work environment that is not yet optimal, an organizational culture that has not gone well, and commitment to the organization that is still low. This study aims to analyze the effect of non-physical work environment and organizational culture on employee performance with commitment to the organization as an intervening variable. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to employees of PT Eka BogaInti in the Bogor area. Data analysis was performed using multiple linear regression techniques. The results showed that the non-physical work environment and organizational culture have a positive and significant influence on employee performance. In addition, commitment to the organization is also proven to mediate the relationship between the non-physical work environment and organizational culture with employee performance. Thus, improving the non-physical work environment and strengthening organizational culture can increase commitment to the organization, which in turn will have a positive impact on employee performance.